Design of the electric propulsion system for dumper trucks - Walter Naranjo Lourido; Luis Ariel Riaño Ocampo; Gustavo Andres Gallego Chipiaje; Javier Eduardo Martinez Baquero; Luis Alfredo Rodriguez Umaña (Institute of Advanced Engineering and Science, 2023)
This article designs a high-efficiency electric propulsion system for industrial trucks, such as dumper trucks. This design proposes using an alternative energy storage system of green H2 hydrogen to reduce emissions. This design determines the propulsion systems' technical and power requirements, starting with each vehicle's driving and duty cycles. For this analysis, a longitudinal dynamic model is created, with which the behavior of the energy conversion chain of the propulsion system is established. The evolutionary methodology analyzes the dynamic forces of vehicle interaction to size the propulsion system's components and the storage system. Using green H2 as fuel allows an energy yield three times higher than diesel. In addition, using this green hydrogen prevents the emission of 264,172 kg of CO₂, which the dumper emits when consuming 1,000 daily gallons of diesel within its working day.